Analisis Peer Influence Dalam Pembelajaran dan Korelasinya Dengan Kinerja dan Motivasi - Yulisna, Gita; Angela, Lia; Pranata, Ogi Danika (Biosfer : Jurnal Biologi dan Pendidikan Biologi, 2024)
Peer influence has a significant impact on students' behavior, attitudes and perceptions of learning. Peer influence is also predicted to be related to students' learning performance and motivation. The support and positive influence of peer influence can provide an important boost for students to reach their full academic potential. This study aims to identify the relationship between peer influence with learning performance and motivation. The method used in this study is a quantitative method with a descriptive and correlational approach. The population consisted of grade X students at SMAN 6 Kerinci and SMAN 4 Sungai Penuh. The sampling technique was conducted using cluster sampling technique. The sample amounted to 175 students from 3 classes of students from each schools. The results showed a positive relationship among the variables. The relationship between peer influence and performance with coefficient of 0.370 and a significance of 0.000, the relationship between peerinfluence and motivation with coefficient of 0.431 and a significance of 0.000, and the relationship between performance and motivation with coefficient of 0.714 and a significance of 0.000. This study found that the stronger the positive influence of peer influence, the higher the performance and motivation of students to learn.